Atomic and Molecular Pulsed Lasers 10th International Conference, Tomsk, Russia, September 12-16, 2011 - Klimkin; Kiseleva (IAO SB RAS, 2011)
Abstracts were printed from the electronic forms presented by the authors. Digest contains the materials on the fundamental and applied problems of pulsed lasers. It is interesting of researches and engineers working in the sphere of quantum electronics, spectroscopy, plasma physics, medicine, remote sensing and laser technologies.